Agaricus blazei polypeptide exerts a protective effect on D‐galactose‐induced aging mice via the Keap1/Nrf2/ARE and P53/Trim32 signaling pathways. Issue 1 (16th November 2020) - Feng, Qingxia; Li, Yingna; Lu, Xuechun; Yu, Ying; Yuan, Guangxin; Sun, Jingbo; Tian, Chenxi; Hu, Lian; Xu, Guangyu; An, Liping; Du, Peige
Abstract: This experiment mainly optimized the extraction technology of Agaricus blazei polypeptide (ABp) and evaluated its protective effect on aging mice. In this study, a novel single component, the M is 3 kD, was isolated and purified from Agaricus blazei. An aging mouse model was established using D‐galactose. After the administration of ABp, the contents of total antioxidant capacity (T‐AOC), malondialdehyde (MDA), catalase (CAT), and reactive oxygen species were significantly changed. Through immunofluorescence staining, it was observed that ABp can reduce changes in brain tissue. The differential expression of genes was analyzed by RNA‐seq. A total of 295 differentially expressed genes were screened out in the ABp group.RT‐qPCR verified important genes and showed that the mRNA expression levels of Hsph1, Trim32, HK1, Hnrnpa1, and Grik5 were significantly increased, and those of ApoE, Atp1a3, Stxbp1, and Mapk8ip1 was significantly decreased. Western blotting showed that the protein expression levels of Keap1 and p53 were significantly lower, while the protein expression levels of Nrf2, HO‐1, Hsph1, and Trim32 were significantly higher in the ABP group. ABp played an anti‐aging role in an aging mouse model. The specific mechanism of action may be related to the regulation of the expression of the Keap1/Nrf2/P53 signaling pathway and related factors. Practical applications: The research may contribute to the development of ABp as functional foods or dietary supplements for anti‐aging in the future. Abstract : The novel peptide monomer isolated from Agaricus blazei Murrill has a significant anti‐aging effect and may act specifically by improving oxidative stress and inflammatory responses. The research may contribute to the development of ABp as functional foods or dietary supplements for anti‐aging in the future.